2017
DOI: 10.1038/jes.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Development of a total hydrocarbon ordinal job-exposure matrix for workers responding to the Deepwater Horizon disaster: The GuLF STUDY

Abstract: Background. The GuLF STUDY is a cohort study investigating the health of workers who responded to the Deepwater Horizon oil spill in the Gulf of Mexico in 2010. Objectives. To develop an ordinal job-exposure matrix (JEM) of airborne total hydrocarbons (THC), dispersants and particulates to estimate study participants’ exposures. Methods. Information was collected on participants’ spill-related tasks. A JEM of exposure groups (EGs) was developed from tasks and THC air measurements taken during and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 10 publications
0
42
0
Order By: Relevance
“…28 From this JEM, various jobs/tasks were assigned TH levels that could vary by time and location. Based on their questionnaire responses, worker exposures to TH could then be determined as a proxy for all petroleum based products encountered.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…28 From this JEM, various jobs/tasks were assigned TH levels that could vary by time and location. Based on their questionnaire responses, worker exposures to TH could then be determined as a proxy for all petroleum based products encountered.…”
Section: Methodsmentioning
confidence: 99%
“…Based on their questionnaire responses, worker exposures to TH could then be determined as a proxy for all petroleum based products encountered. 28 The present analysis used the maximum TH level for each worker, across all tasks and time periods. 28 Additionally, industrial hygienists classified participants into 6 OSRC job groups and also by likely exposure to burning oil.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BP contractors collected a large number of measurements on the personal airborne exposure of oil spill response/clean-up workers and scientists to total hydrocarbons. Results from a subset of the dosimeter badges indicated that workers in Louisiana were exposed to average total hydrocarbon levels 2 to 4 times higher than similar workers in Florida over the period of 20 April through 10 August, and substantially more than background levels prior to the spill (Stewart et al 2017). This analysis was limited to the subset of individuals working on small vessels working near the shoreline that were not involved in decontamination activities, because these most closely mimicked potential dolphin exposure.…”
Section: Inhalationmentioning
confidence: 99%